Case report and literature review of Ewing's sarcoma in the gastrointestinal tract. Issue 2 (30th December 2017) - Bong, Christopher; Thomson, Iain; Lampe, Guy
Abstract : We present a case of a young female patient with extraosseous Ewing's sarcoma (EES) arising in the lesser sac, as confirmed by membranous staining for CD99 and an ESWR1 gene translocation on fluorescence in situ hybridization. We also provide comprehensive review of the English literature of Ewing's sarcoma (ES) occurring in the gastrointestinal tract (GIT). A systematic review of the PubMed database was carried out with the following MeSH terms: Ewing's AND sarcoma AND (oesophagus, stomach, small bowel OR intestine, large bowel OR intestine, colon, sigmoid, rectum, pancreas, peritoneum, lesser sac, greater sac, liver and gallbladder). Fifty‐seven cases were collated from 46 articles. The most common overall symptom was pain (60.71 per cent), which occurred in patients as young as 2 years and as old as 72 years. The median age was 31 years, and the mean age was 29 years. No bimodal distribution was demonstrated. More females appeared to be affected than males. EES of the GIT is rare. It differs from ES with respect to patient age and sex. No standard therapy for EES has been widely adopted.